Implementasi Kebijakan Proses Perencanaan Dan Penganggaran Pada Biro Sistem Informasi, Perencanaan Dan Pengembangan Universitas Sumatera Utara Medan - Zulkhairi Nasution; Badaruddin Badaruddin; Budi Hartono (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine and analyze the Implementation of Planning and Budgeting Process Policies at the Information Systems Bureau, Planning and Development of the University of North Sumatra Medan and to find out what factors are the obstacles / obstacles in the Implementation of the Planning and Budgeting Process Policy at the Bureau of Information Systems, Planning and Development, University of North Sumatra Medan. The research method used is a descriptive method with a qualitative approach, with research informants being the Head of Bureau, Head of Section, Head of Subdivision and Staff at the Bureau of Information Systems, Planning and Development, University of North Sumatra, Medan. The theory used is George C Edward III's public policy theory. The results of this study indicate that the Planning and Budgeting Process Policy Implementation at the Information Systems, Planning and Development Bureau has been implemented but has not achieved optimal results. The success of policy implementation needs to be supported by the authority and SOP for Planning and Budgeting at the Information Systems, Planning and Development Bureau at USU Medan. The factors that influence the Implementation of Planning and Budgeting Policies at the Bureau of Information Systems, Planning and Development of the University of North Sumatra are communication, disposition, resources, and bureaucratic structure. Good communication distribution and good coordination between leadership and staff are needed in order to produce a good implementation, therefore it is recommended to issue a Standard Operating Procedure (SOP) for planning and budgeting process policies in order to provide optimal results in the planning and budgeting process.